The preliminary long-term slow drift calibration study in low- level RF system. (November 2019) - Lin, Z.Y.; Du, Y. C.; Huang, W.H.; Tang, J.H.; Tang, C.X.; Huang, G.; Xu, Y.L; Zhang, D.; Sun, Z.C.
Abstract: The phase drift of the RF signal in the low-level radio frequency (LLRF) system is observed in the long-term operation, which limits the performance and stability of the LLRF system. The long-term drift was reproduced in the lab. Its effect and sources of error were explored in the simple LLRF46 board and the simplest LLRF system. It is founded that the temperature will significantly lead to the phase distortion of the two signal channels, although with the same electron device. The distortion will finally cause the long-term drift with temperature floating. A fixed phase calibration signal (CAL signal) is applied to deal with the signal channels difference. The preliminary tests were conducted and the results were analysed.